Against trauma: silence, victimhood, and (photo-)voice in northern Namibia - Becker, Heike (University of the Free State, 2015)
The article shows how the discourses of trauma, victimhood and silence regarding local agency contributed to the production of the nationalist master narrative in postcolonial Namibia. However, I point out repositories of memory beyond the narratives of victimhood and trauma, which began to add different layers to the political economy of silence and remembrance in the mid-2000s. Through revisiting visual forms of remembrance in northern Namibia an argument is developed, which challenges the dichotomy between silence and confession. It raises critical questions about the prominent place that the trauma trope has attained in memory studies, with reference to work by international memory studies scholars such as Paul Antze and Michael Lambek (1996) and South African researchers of memory politics, particularly the strategies of the Truth and Reconciliation Commission (TRC). The fresh Namibian material supports the key critique of the TRC, which suggests that the foregrounding of pain and victimhood, and rituals of therapy and healing entailed a loss of the political framings of the testimonial moments.
Keywords: Trauma; Victims; Silence; Namibia; Truth and Reconciliation Commission (TRC)